Administering NetWare 5 - Cady, Dorothy (McGraw-Hill, 2000)
Like all of the Administering books, Administering Netware 5 uses a task-oriented approach to introduce and explain NetWare 5. The book includes many helpful features, such as walkthroughs, which provide step-by-step instructions for gaining hands-on experience. Task-based section titles help guide readers quickly to the subjects they need help with. Loads of screen shots and figures make the book useful both near and away from the console. Finally, extensive "for more information" sections point readers to useful Web sites and periodicals.